Pulmonary function of automobile repair workers in the informal sector of Raichur urban - M. K., Krishna Kumar; George, Leyanna Susan (International Journal Of Community Medicine And Public Health, 2017)
Background: Automobile repair workers of the informal sector are exposed to dusts, toxic fumes and aerosols. Long term occupational exposure may lead to pulmonary function impairment. Hence, the objectives were to study the occurrence of obstructive and restrictive pulmonary impairment among the automobile repair workers by using pulmonary function test and the factors associated with it. Methods: A cross sectional study was carried out in automobile repair workers who work in informal sector in the urban area of Raichur in Karnataka. The pulmonary function tests viz. Forced Expiratory volume in one second, Forced vital capacity, Peak Expiratory Flow Rate per liter and FEV1/FVC ratio in percentage were measured for each worker in sitting posture using a digital spirometer. Data collected were analyzed in SPSS 16.0 software. Chi-square test and t test was used. Results: Out of the 97 automobile repair workers, 42 (43.3%) had normal pulmonary function. Among the abnormal PFT, 20 (20.6%) had obstructive lung function, 25 (25.8%) had restrictive lung function and 10 (10.3%) had mixed obstructive and restrictive lung function. The workers with abnormal PFT consisted of body repair workers (25.0%), mechanical workers (38.1%), spray painters (75.0%), battery repair workers (100.0%) and tyre retreading workers (88.9%). Conclusions: In this study, 56.7% of workers had some form of pulmonary function impairment. Smoking, increase in duration of work hours and years of work showed significant pulmonary impairment. The study highlights the need for creating awareness and encouraging the use of protective gears such as masks, early screening, diagnosis and treatment of respiratory diseases among the garage workers.